The potential of ridership attraction for bus rapid transit system (BRT) in Iskandar Malaysia : examining the image and perception - Amir Hamzah Amirrudin, 1994-, author; Zuhra Junaida Muhamad Husny Hamid, 1974-, supervisor; Fakulti Alam Bina (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Project Paper (Sarjana Muda Perancangan Bandar Dan Wilayah) - Universiti Teknologi Malaysia, 2018